Contract fulfilment, quality management, ICT adoption, government, and co-worker support: a conceptual framework for student contentment in higher educational institutions - Samuel Koomson (Cogent Business & Management, 2024)
This paper examines the direct effect of employees' psychological contract fulfilment (PCF) on student contentment (CON), exploring the mediating roles of total quality management (TQM) and information communication technology (ICT) adoption, and moderating roles of government support (GOS) and co-worker support (COS) in higher educational institutions (HEIs) worldwide. The paper develops a conceptual framework along with postulations by combining both empirical and theoretical literature in multidisciplinary fields. This paper finds and proposes that PCF will be positively related to CON, and this positive relationship will be positively mediated by TQM and ICT adoption jointly and independently. Additionally, GOS and COS will positively moderate between PCF and CON. This paper lays the foundation for upcoming researchers to empirically test the proposed conceptual framework in different educational settings across the globe. The conceptual research bridges the gap between educational management literature and other fields such as quality management, information systems, and public administration. It helps HEIs prioritise initiatives that enhance the overall well-being of their staff and faculty. This puts them in a better position to satisfy students. This advances Sustainable Development Goal 4, which aims to guarantee inclusive and fair quality education and encourage endless possibilities for learning for every student.Education is a crucial component of society, and the satisfaction of both educators and students can have broader societal implications. This research highlights the need for policies or practices that support educators in meeting their psychological needs, ultimately benefiting society at large. For instance, this paper will be of interest to parents who want the best possible educational experience for their children. The media often covers topics related to education and workplace dynamics. This study will attract public attention and become part of broader discussions on education reform. Policymakers should consider initiatives that support educators in meeting their needs. This information could be applicable to other professions as well, emphasizing the significance of meeting employees' psychological needs.
Keywords: 650; higher educational institutions; employer-employee relations; continuous improvement; government support; co-worker support; customer satisfaction; information technology; interdisciplinary; conceptual framework